SAFE HAVEN OR SELECTIVE SHIELD? INSTITUTIONAL INVESTOR HETEROGENEITY, GEOPOLITICAL RISK, AND THE CRISIS RESILIENCE OF GREEN BONDS (World Economics and Finance Bulletin, 2026)
The rapid expansion of green bonds positions sustainable finance at the coreof climate mitigation strategies. However, empirical evidence on their crisisresilience and corporate value effects remains contradictory. This studysynthesizes 73 peer-reviewed articles using meta-analytical methods (randomeffects models, FAT-PET, PEESE) to resolve these discrepancies. We proposeand test the Asymmetric Shock Resilience Hypothesis: green bonds exhibitdiametrically opposite behaviors depending on shock origin